LIMBERG FLAP TECHNIQUE FOR PILONIDAL SINUS DISEASE TREATMENT: AN EXPERIENCE OF HAMDARD UNIVERSITY HOSPITAL - Zubair, Rabbia; Channa, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2022)
Background: Pilonidal sinus disease (PNSD) is considered as the challenging disease for surgeons since decades. The term pilo-nidal is derived from Latin meaning nest of hair. It is a commonly occurring disease usually involved young male adults. It is considered as an acquired condition with unidentified aetiology and pathogenesis. The objective was to observe the results of Limberg’s flap operation in patients with Pilonidal sinus disease. Methods: We performed an observational study at Hamdard University Hospital from 1st January 2016 to 31st December 2019 on patients who came to the outpatient department for the treatment of pilonidal sinus diseases and underwent surgery (Limberg’s flap) after consent. The patient’s presentation varied from single sinus and dry, multiple sinuses and dry, single sinus with serous discharge, single sinus with pus discharge, and pilonidal abscess. Forty-six patients were selected after applying inclusion and exclusion criteria and operated by Limberg’s flap technique. Result: Results were observed for postoperative seroma, hematoma, wound infection, persistent pain, and recurrence. Out of 46 patients, 30 (65.21%) were male and 16 (34.7%) were female. 28 patients (60.8%) were between 31-40 years of age and 12 patients (26.08%) were between 41-50 years of age. After performing Limberg’s flap procedure, 35 patients (76%) had no complications at all. 2 patients (4.3%) had seroma formation. 4 patients had Hematoma formation (8.6%). Two patients (4.3%) patients developed superficial wound infection. 2 patients (4.3%) had persistent pain after 3 months of the procedure. One patient (2.1%) had recurrence during the follow-up period of 12 months. Conclusion: Limberg’s flap operation is associated with low recurrence as well as a low rate of other complications such as seroma or hematoma formation, wound infection, and persistent pain irrespective of the presentation of the pilonidal sinus.